2020
DOI: 10.1002/jcp.29530
|View full text |Cite
|
Sign up to set email alerts
|

Activation of CB2R with AM1241 ameliorates neurodegeneration via the Xist/miR‐133b‐3p/Pitx3 axis

Abstract: Activation of cannabinoid receptor type II (CB2R) by AM1241 has been demonstrated to protect dopaminergic neurons in Parkinson's disease (PD) animals.However, the specific mechanisms of the action of the CB2R agonist AM1241 for PD treatment have not been characterized. Wild-type (WT), CB1R knockout (CB1-KO), and CB2R knockout (CB2-KO) mice were exposed to 1-methyl-4-phenyl-1,2,3, 6-tetrahydropyridine (MPTP) for 1 week to obtain a PD mouse model. The therapeutic effects of AM1241 were evaluated in each group. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Similar observations were found in a study of CB 2 receptors in cerebral malaria, where the benefits were reached by blocking the receptor or ablating its gene expression [2]. However, this contrasts with most of the literature on CB 2 receptor in other neurodegenerative/neuroinflammatory disorders, in which the benefits were reached after the activation of this receptor [6,14,25,28,32,50]. The difference compared with our current study may be in the cell type where the CB 2 receptor is located: glial versus neuronal location.…”
Section: Discussionsupporting
confidence: 66%
“…Similar observations were found in a study of CB 2 receptors in cerebral malaria, where the benefits were reached by blocking the receptor or ablating its gene expression [2]. However, this contrasts with most of the literature on CB 2 receptor in other neurodegenerative/neuroinflammatory disorders, in which the benefits were reached after the activation of this receptor [6,14,25,28,32,50]. The difference compared with our current study may be in the cell type where the CB 2 receptor is located: glial versus neuronal location.…”
Section: Discussionsupporting
confidence: 66%
“…The number of registered clinical trials indicated in https://clinicaltrials.gov/ for testing cannabidiol in a variety of pathological conditions is 321 (date: 1 July 2021). As commented in the introduction, the CB 2 R is, also, an attractive target to afford neuroprotection in Parkinson's disease [3,[7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…The CB 2 R is considered a target for neuroprotection, especially in diseases coursing with neuroinflammation. For instance, cannabinoids acting on the CB 2 R in striatal neural cells reduce the neuronal loss in synucleinopathies such as Parkinson's disease [8][9][10][11][12][13]. The underlying mechanism is mainly related to the reduction of inflammation, but the CB 2 R expressed in some striatal neurons may also have a relevant role [3,7,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Trisomy 21, Pitx3, TLR5, TNFAIP1, STAT3, ZEB1 Jin et al, 2018;Yan et al, 2018;Wei et al, 2019 Neurodegeneration miR-133b-3p Pitx3 He et al, 2020 Alzheimer's disease miR-132, miR-124 BACE1 Wang et al, 2018b;Du Y. et al, 2020Osteoarthritis miR-211, miR-214-3p, miR-17-5p, miR-1277 CXCR4, MAPK, AHNAK, BMP2, TIMP-3, MMP-13, ADAMTS5, OPN, SGTB, DNMT3A, GNG5 Liao et al, 2019;Wang et al, 2019e;Feng et al, 2020;Ghaderian et al, 2020;Li et al, 2020b;Liu et al, 2020e;Shen X.F. et al, 2020 Bone marrow miR-9-5p ALPL, ALP, Bglap, Runx2 Zheng C. et al, 2020 Inflammation miR-27a-3p, miR-34a, miR-30c-5p, miR-146a NF−κB, NLRP3, Smurf1, YY1, PTEN, Nav1.7 Shenoda et al, 2018;Sun W.B.…”
Section: Lncrna Xist In Neuropathic Painmentioning
confidence: 99%
“…In Down’s syndrome, lncRNA Xist ( Czerminski and Lawrence, 2020 ), which fully corrects trisomy 21 dosage in neural cells, promotes differentiation of trisomic NSCs (neural stem cells) to neurons by silencing Trisomy 21 and activating Notch signaling pathway. In Parkinson’s disease (PD) animals, it has been shown that lncRNA Xist/miR-133b-3p/Pitx3 axis protect dopaminergic neurons through activation of CB2R with AM1241, which alleviates PD ( He et al, 2020 ). In addition, lncRNA Xist participated in neuropathic pain though interacting with miRNAs in CCI (chronic constriction injury) rat models, including miR-154-5p, miR-137, miR-544, and miR-150.…”
Section: The Role Of Lncrna Xist In Non-cancer Diseasesmentioning
confidence: 99%